BENCHMARKING OF "SINGLE CHECKER" PATIENT GROUP DIRECTIONS (PGDS) DURING INITIAL NURSE ASSESSMENT WITHIN PERUKI EDS. Issue 12 (23rd November 2015) - Bird, C; Hartshorn, S
Abstract : Objectives & Background: New ways to optimise ED patient flow, without sacrificing quality of care, are at a premium.1 Doubt has been cast on the efficacy of double checking in all but high risk medications, 2 and a study in Geelong, Australia, showed no difference in error rates between double-checked and single-checked medications.3 We aimed to benchmark single-checked PGD medications at triage within PERUKI EDs (Paediatric Emergency Research in the UK and Ireland). A PGD is a legal instruction that allows the supply/administration of a select group of licensed medicines by a select group of healthcare professions, approved beforehand by a doctor, to groups of patients who might not be identified individually prior to presentation. Methods: Online survey distributed to the research representative at each PERUKI site. The survey was open for 5 weeks (March–April 2015) and was completed by any appropriate clinician within the site. Results: The response rate was 84% (36 out of 43 EDs). From these, 22 out of 36 EDs (61%) were using single-checker PGDs. The commonest single-checker medications in use were paracetamol and ibuprofen for pain (Figure 1). 22% of EDs reported drug errors related to standard (double-checked) PGDs, while 14% of those with single-checked PGDs reported drug errors. The commonest errors reported were: duplicated dose, incorrect weight, incorrect volume drawn up, contraindication missed. Barriers to single-checked medications in the 11 EDs that did not use them included lack of training courses, lack of staffing in pharmacy for policy preparation and variation in practice from other paediatric areas. Conclusion: Single checker PGDs are currently in use in nearly two thirds of PERUKI sites, with no evidence for increased medication errors with their use. Barriers to the introduction of this practice, together with solutions, have been shared amongst all PERUKI sites.Figure 1